The Mediating Effect of Motivation and Competitive Experience Variables on The Effect of Mental Toughness and Competitive Anxiety on Athletes - Nugraha, Dwi Yan; Salman, Randy S.; Pratama J, Bambang; Al Fayed, Muhammad Gilang; Ikhram, Aidil; Bahrun, Muhammad Irfan; Ridwan, Fadila Khumaera; S, Nurlifiana (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2020)
The purpose of this study is to examine whether mental toughness can predict competitive anxiety through the motivation and competitive experience possessed by athletes. Respondents involved were 175 athletes who were students (93 female and 82 male). Path analysis reports that there are direct and indirect effects of the measured variable. Our results show the influence of mental toughness on competitive anxiety. However, the influence of exerted is a positive effect that if athletes have good mental toughness, then their competitive anxiety increases as well. Researchers suspect that there are other constructs that accompany mental toughness in influencing competitive anxiety in athletes. The mediation model also shows that athletes who have high motivation and competitive experience significantly mediate the influence between mental toughness and athlete’s competitive anxiety. Concluded that mental toughness, motivation, competitive experience, have a reciprocal relationship from competitive anxiety. In addition, the results of this study also reported that mental toughness, motivation, and competitive experience are able to predict competitive anxiety.